National Survey Assessing Treatment of Helicobacter pylori Infection in Korean Children: A Pilot Study - Jong-Hyuk Youn; Sin Jae Kim; Ji-Hyun Seo; Jae-Young Kim; Hee-Shang Youn; Jae Sung Ko; Kyung Mo Kim; Ju-Young Chung (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: The standard guideline for the management Helicobacter pylori infection in Korean children is not present until now. In present study, we conducted the questionnaire survey to investigate the real situation of H. pylori eradication in children. Materials and Methods: Questionnaire concerning the indications of H. pylori eradication, the first choice of treatment modality, the decision method of eradication result, experience of eradication failure, the second choice of treatment modality was sent to doctors who are members of the Korean Society for Pediatric Gastorenterology, Hepatology, and Nutrition. Results: A total of 28 doctors (90.3%) answered the questionnaires among 31 doctors. The most common indication for eradication of H. pylori was peptic ulcer (n=24) followed by chronic abdominal pain (n=17) and positive family history of gastric cancer (n=12). The most common choice of first-line eradication therapy was omeprazole, amoxicillin, clarithromycin triple therapy (n=21) and followed by bismuth subsalicylate, amoxicillin, metronidazole, clarithromycin quadruple therapy (n=7). The results of treatment were judged by C¹³-urea breath test after 2 months later in 19 doctors (67.8%). Twenty four (85.7%) out of 28 doctors had experienced treatment failure. The most common second-line therapy was the sequential therapy (58.3%, 14 doctors among 24). Conclusions: This was the first study for the survey of the treatment of H. pylori infection to Korean pediatricians. The results of this study showed that most pediatric gastroenterologists used to treat H. pylori infection according to the textbook and the common use of bismuth-based quadruple therapy for the first-line treatment was notable.